Instruction to start the work at BRACU new campus project (BBT system) - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the instruction to start the work of supply, installation, testing and commissioning of Busbar Trunking (BBT) System for BRACU new campus project.